Learning Networking System Created by Some Universities in Indonesia - M. Oky F. Gafari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Learning in Higher Education to date, continues to grow following the rapid flow of globalization of digital technology. The form of digitalization of the learning process will later penetrate the boundaries of space and time that have been insulating the interaction between lecturers and students. This simple writing, then will describe the design of the digital learning process in college. Digitalization referred to in this paper is an Android-based learning design utilizing software / learning management system (LMS) for activities in the network (online) in Indonesian phonology courses. Some features that can be utilized in managing LMS-based learning are: a) Courses, with menu courses, users can create new classes, join classes that have already existed or browse through the predefined class list. b) Groups, functions like group member wall messages and can also post wall messages. When joining a group, users can search for parts of the group that the user wants.